Digital Transformation in Smart Manufacturing - Petrillo, Antonella; Cioffi, Raffaele; De Felice, Fabio (IntechOpen, 2018)
The purpose of this book is to provide an overview of the new industrial revolution: the "Industry 4.0." Globalization and competitiveness are forcing companies to review and improve their production processes. Industry 4.0 is a revolution that involves many different sectors and is still evolving. It represents the integration of tools already used in the past (big data, cloud, robot, 3D printing, simulation, etc.) that are now connected to a smart network by transmitting digital data at high speeds. The implementation of a 4.0 system represents a huge change for companies, which are faced with big investments. The idea of the book is to present practices, challenges, and opportunities related to the Industry 4.0. This book is intended to be a useful resource for anyone who deals with this issue.